STUDI ANALISIS KELAYAKAN FINANSIAL USAHA BUDIDAYA UDANG VANAME (L. vannamei) DI TAMBAK PESISIR KOTA PEKALONGAN - Permatasari, Mahardhika Nur; Ariadi, Heri (Universitas Sam Ratulangi, 2021)
AbstractThe vaname shrimp (L. vannamei) culture on the Pekalongan coast has begun to be carried out and developed more intensively. The purpose of this study was to determine the financial feasibility status of vaname shrimp farming business in coastal region of Pekalongan City, Central Java. The research method used in this research is descriptive quantitative and descriptive qualitative with purposive sampling data collection techniques. The parameters observed are water quality parameters and indicators of business financial feasibility analysis. The results of this study, obtained the pH value of pond water 8.3, salinity 15 ppt, dissolved oxygen >4 mg/L, green water colour, and water level of 120 cm or the quality standard is appropriate for operational shrimp farming. Meanwhile, from the results of the financial feasibility analysis of the business, the profit value of Rp. 443,992,208, R/C Ratio 1.74, BEP unit 2,729 kg, BEP sales Rp. 149,618,403, business profitability 7.4, Net Present Value Rp. 35,391,189,367, Payback Periods 3.1 years, and Profitably Index 48.36% means that this business unit is very feasible and profitable. Based on the analysis of the financial feasibility of the business and the existing water quality parameter profile, the vannamei shrimp farming business unit in coastal region of Pekalongan City, Central Java is very feasible and profitable to run and develop in the future. Keywords: Coastal, financial feasibility, L. vannamei, vaname shrimp AbstrakBudidaya udang vaname (L. vannamei) di pesisir Kota Pekalongan mulai marak dijalankan dan dikembangkan lebih intensif. Tujuan dari penelitian ini adalah untuk mengetahui status kelayakan finansial unit usaha budidaya udang vaname di tambak pesisir Kota Pekalongan, Jawa Tengah. Metode peenlitian yang digunakan dalam penelitian ini adalah deskriptif kuantitatif dan deskriptif kualitatif dengan teknik pengambilan data secara purposive sampling. Adapun parameter yang diamati adalah parameter kualitas air dan indikator-indikator analisis kelayakan finansial usaha.Hasil dari peenlitian ini, didapatkan nilai pH air tambak 8.3, salinitas 15 ppt, oksigen terlarut >4 mg/L, warna air hijau, dan ketinggian air 120 cm atau secara baku mutu sudah sesuai untuk kegiatan budidaya udang. Sedangkan dari hasil analisis kelayakan finansial usaha didapatkan nilai keuntungan Rp. 443.992.208, R/C Ratio 1.74, BEP unit 2.729 kg, BEP sales Rp. 149.618.403, rentabilitas usaha 7.4, Net Present Value Rp. 35.391.189.367, Payback Periods 3.1 tahun, dan Profitabily Index 48.36% artinya unit usaha ini sangat layak dan menguntungkan. Berdasarkan analisis kelayakan finansial usaha dan profil parameter kualitas air yang ada, unit usaha budidaya udang vaname di tambak pesisir Kota Pekalongan, Jawa Tengah sangat layak dan menguntungkan untuk dijalankan serta dikembangkan di masa yang mendatang. Kata kunci: Pesisir; kelayakan finansial; L. vannamei; udang vaname